The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.pbiomolbio.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of new generation transgenic methods on creating rabbit models of cardiac diseases

Abstract: Since the creation of the first transgenic rabbit thirty years ago, pronuclear microinjection remained the single applied method and resulted in numerous important rabbit models of human diseases, including cardiac deficiencies, albeit with low efficiency. For additive transgenesis a novel transposon mediated method, e.g., the Sleeping Beauty transgenesis, increased the efficiency, and its application to create cardiac disease models is expected in the near future. The targeted genome engineering nuclease fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
(78 reference statements)
0
17
0
2
Order By: Relevance
“…Additionally, rabbit cardiomyocyte ultrastructure (for example, of the T-tub system) is closely reminiscent of that in human cells ( 49 ). As a consequence, there is a growing appreciation for the utility of rabbit models to study basic electrophysiological concepts, human heritable diseases ( 50 ), and for preclinical cardiac safety testing ( 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, rabbit cardiomyocyte ultrastructure (for example, of the T-tub system) is closely reminiscent of that in human cells ( 49 ). As a consequence, there is a growing appreciation for the utility of rabbit models to study basic electrophysiological concepts, human heritable diseases ( 50 ), and for preclinical cardiac safety testing ( 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…Первый трансгенный кролик был получен микроинъекцией (МИ) конструкции ДНК в пронуклеус зиготы еще в 1985 г. [29], однако эффективность получения трансгенных (ТГ) животных классическим трансгенезом длительное время оставалась низкой [12,33]. В отличие от мышей технологии использования эмбриональных стволовых клеток (ESС) на кроликах практически не работали, метод переноса ядер соматических клеток (SCNT) имел очень низкую эффективность [16,30,99].…”
Section: недалекая история трансгеноза и геномного редактирования кроunclassified
“…Первый кролик с нокаутом гена (knockout, KO) был получен методом SCNT только в 2015 году [94]. Тем временем стремительно развивающиеся методы редактирования генома позволили получать KO-гены у разных видов животных, в т. ч. и кроликов [12,32].…”
Section: недалекая история трансгеноза и геномного редактирования кроunclassified
“…Regardless of the demand for genetically-modified rabbit, naturally occurring or spontaneous mutant strains were only available (Bosze and Houdebine 2006 ). Since the first transgenic rabbit was produced through the pronuclear microinjection of a DNA construct (Hammer et al 1985 ), some methodological improvements have been reported for rabbit transgenesis (Viglietta et al 1997 ; Besenfelder et al 1998 ); however, it is still characterized by too-low transgenic efficiency (Houdebine and Fan 2009 ; Bosze et al 2016 ). As the lack of fully functional rabbit ES cells was not produced (Honda et al 2013 ; Honsho et al 2015 ) and somatic cell nuclear transfer (SCNT) technologies are not established in rabbits (Zakhartchenko et al 2011 ), still the targeted genome editing was not possible before the application of engineered endonucleases.…”
Section: Rabbitmentioning
confidence: 99%